2014
DOI: 10.1371/journal.pgen.1004165
|View full text |Cite|
|
Sign up to set email alerts
|

Mammalian E-type Cyclins Control Chromosome Pairing, Telomere Stability and CDK2 Localization in Male Meiosis

Abstract: Loss of function of cyclin E1 or E2, important regulators of the mitotic cell cycle, yields viable mice, but E2-deficient males display reduced fertility. To elucidate the role of E-type cyclins during spermatogenesis, we characterized their expression patterns and produced additional deletions of Ccne1 and Ccne2 alleles in the germline, revealing unexpected meiotic functions. While Ccne2 mRNA and protein are abundantly expressed in spermatocytes, Ccne1 mRNA is present but its protein is detected only at low l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 45 publications
3
73
1
Order By: Relevance
“…It has been reported that E-type cyclins (E1 and E2) also form complexes with Cdk2 in mouse spermatocytes, and the knockout mice for Ccne1 and Ccne2 partially mimic the phenotypes seen in Cdk2 −/− spermatocytes, suggesting the involvement of canonical cyclins in the activation of Cdk2 during meiosis (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that E-type cyclins (E1 and E2) also form complexes with Cdk2 in mouse spermatocytes, and the knockout mice for Ccne1 and Ccne2 partially mimic the phenotypes seen in Cdk2 −/− spermatocytes, suggesting the involvement of canonical cyclins in the activation of Cdk2 during meiosis (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Each reaction was performed in triplicate. The values were normalized to the expression of the gene encoding ribosomal protein, large, P0 (Rplp0) (also named Arbp, acidic ribosomal phosphoprotein P0) as an internal control as previously reported (15)(16)(17)(18)(19). Statistical analyses were performed with two-way ANOVA followed by Tukey's comparisons test (GraphPad Prism software) as discussed below in the Statistical Analysis section.…”
Section: Quantitative Real-time Pcr From Paraformaldehydefixed Parafmentioning
confidence: 99%
“…In contrast to their overlapping expression in somatic cells, we previously reported that E-type cyclins exhibit distinct patterns of expression in the germ line, notably in meiotic spermatocytes rather than in mitotic spermatogonia (Martinerie et al 2014). Cyclin E1 expression is restricted to non-proliferating Sertoli cells and mid-pachytene to diplotene spermatocytes, where it is specifically localized along the axial element of the sex chromosomes.…”
Section: Introductionmentioning
confidence: 89%
“…Indeed, using constitutive and conditional knockout mice lines, we observed that cyclin E2-deficient ( E1+/+E2−/− ) males exhibited reduced fertility (Geng et al 2003; Martinerie et al 2014) resulting from meiotic defects in homologue pairing, synapsis and DNA repair (Martinerie et al 2014). The relevance of both E-type cyclins for male meiosis is also underscored by our observations that the additional loss of one E1 allele ( E1+/−E2−/− ) resulted in sterility, with severely disrupted spermatogenesis and enhanced meiotic defects (Martinerie et al 2014). The complete absence of E-type cyclins in the male germ line resulted in a meiotic catastrophe, with most spermatocytes arrested at zygotene and early pachytene-like stages.…”
Section: Introductionmentioning
confidence: 99%